Towards Effective Counseling Approaches and Contextual Factors Enhanced Diversity Collaboration - Mohamed Sharif, Mustaffa; Md Rahimullah, Miah; Amalia, Madihie; Yadav, Prashanth Talwar (Science Publishing Corporation Inc, 2018)
This study explored the counselling approach and contextual factors to enhance diversity collaborations among ethnic, religious people, teachers and parental involvement in Malaysian secondary schools. Specially, the study outlined cross-cultural counselling and related training approaches and effective factors that needs in Malaysian society. In particular, the researcher investigated the effectiveness of multi-ethnicity of students and diversity of approaches in their counselling contexts. Qualitative data were obtained from field survey while secondary data collected from various sources. The study focuses the main difficulties in general contextual literature, theoretical or ideological, and collaborative diversity approaches showing in the countries concerned. A qualitative case study approach was also represented on the experience of counsellors of eleven muslim schools in the Muar district through primary and secondary data analysis. The study recommended that effective counselling environment context enhanced diversity collaboration with their training models in various ways in relation to the contextual factors studied.